2019
DOI: 10.3892/or.2019.7184
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a murine model of BCR‑ABL1+ acute B‑lymphoblastic leukemia with central nervous system metastasis

Abstract: Breakpoint cluster region (BCR)-Abelson murine leukemia (ABL)1 + acute B-lymphoblastic leukemia (B-ALL) is a disease associated with a dismal prognosis and a high incidence of central nervous system (CNS) metastasis. However, BCR-ABL1 + B-ALL with CNS infiltration has not been previously characterized, at least to the best of our knowledge. In the present study, a murine model of BCR-ABL1 + B-ALL with CNS metastasis was established using retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…However, it appears that CNS disease in BCR-ABL1-positive ALL shares some common features and pathways with other cytogenetic subtypes with CNS tropism. Different in vivo model systems of BCR-ABL-positive ALL based on the introduction of a BCR-ABL1 fusion gene into murine bone marrow cells showed profound infiltration of the CNS [39,57]. One study in a mouse model of BCR-ABL positive leukemia with CNS tropism found the upregulation of L-selectin and integrin subunit alpha 6 (Itga6) in BCR-ABL expressing cells compared to control cells [57].…”
Section: The Relevance Of Cytogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it appears that CNS disease in BCR-ABL1-positive ALL shares some common features and pathways with other cytogenetic subtypes with CNS tropism. Different in vivo model systems of BCR-ABL-positive ALL based on the introduction of a BCR-ABL1 fusion gene into murine bone marrow cells showed profound infiltration of the CNS [39,57]. One study in a mouse model of BCR-ABL positive leukemia with CNS tropism found the upregulation of L-selectin and integrin subunit alpha 6 (Itga6) in BCR-ABL expressing cells compared to control cells [57].…”
Section: The Relevance Of Cytogeneticsmentioning
confidence: 99%
“…Different in vivo model systems of BCR-ABL-positive ALL based on the introduction of a BCR-ABL1 fusion gene into murine bone marrow cells showed profound infiltration of the CNS [39,57]. One study in a mouse model of BCR-ABL positive leukemia with CNS tropism found the upregulation of L-selectin and integrin subunit alpha 6 (Itga6) in BCR-ABL expressing cells compared to control cells [57]. By this, BCR-ABL-positive cells may be prone to adhere to CNS vessels and to utilize the vascular entry routes described above.…”
Section: The Relevance Of Cytogeneticsmentioning
confidence: 99%
“…The absence of ITGA6 in BM and CSF supernatants gained by cell removal in our study claims that this cell surface protein of blast cells may not be likely to be involved in integrin shedding or such process allocating ITGA6 into the extracellular space. Previously, high ITGA6 expressions were measured inside the CNS-invading leukemic cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALL xenografts treated with specific α6 integrinneutralizing antibodies showed reduced leukemia burden in the CSF/meninges. High levels of Itga6 mRNA (encodes α6) were also found in leukemic cells in a BCR-ABL1-driven murine model of meningeal leukemia (Yu et al, 2019). On the contrary, recent studies identified ITGA5 (α5) and ITGA9 (α9) expression positively correlated with CSF colonization in primary B-ALL samples (Scharff et al, 2020a;Scharff et al, 2020b).…”
Section: Cell Adhesion In Leukemic Cell Colonization Of the Central Nervous Systemmentioning
confidence: 99%